Implementasi Pendidikan Islam Moderat Bagi Generasi Milenial NU di Desa Semat Tahunan Jepara - Ahmad Saefudin; Umi Ma’rufiani Dewi (Jurnal Pendidikan : Riset dan Konseptual, 2023)
This article aims to explore the implementation of moderate Islamic education for the NU millennial generation in Semat Village, Tahunan, Jepara. This study uses a qualitative approach by collecting data through interviews and observations. The results of the study show that the NU millennial generation in Semat Village applies moderate Islamic education through recognition of other parties, respect for the opinions of others, tolerance towards ethnicity, race, culture, and beliefs, and rejecting violence as a way to impose one's will. The theoretical implication of this research is to strengthen the understanding of the importance of moderate Islamic education in maintaining interfaith harmony. However, this study has limitations in generalizing the results only to the context of the Semat Tahunan Jepara Village and limitations in the number of samples. Further research with a wider scope is needed to obtain a more comprehensive picture of the implementation of religious moderation for the NU millennial generation.